Global variation in freshwater physico‐chemistry and its influence on chemical toxicity in aquatic wildlife. (4th May 2021) - Pinheiro, João Paulo S.; Windsor, Fredric M.; Wilson, Rod W.; Tyler, Charles R.
ABSTRACT: Chemical pollution is one of the major threats to global freshwater biodiversity and will be exacerbated through changes in temperature and rainfall patterns, acid–base chemistry, and reduced freshwater availability due to climate change. In this review we show how physico‐chemical features of natural fresh waters, including pH, temperature, oxygen, carbon dioxide, divalent cations, anions, carbonate alkalinity, salinity and dissolved organic matter, can affect the environmental risk to aquatic wildlife of pollutant chemicals. We evidence how these features of freshwater physico‐chemistry directly and/or indirectly affect the solubility, speciation, bioavailability and uptake of chemicals [including via alterations in the trans‐epithelial electric potential (TEP) across the gills or skin] as well as the internal physiology/biochemistry of the organisms, and hence ultimately toxicity. We also show how toxicity can vary with species and ontogeny. We use a new database of global freshwater chemistry (GLORICH) to demonstrate the huge variability (often >1000‐fold) for these physico‐chemical variables in natural fresh waters, and hence their importance to ecotoxicology. We emphasise that a better understanding of chemical toxicity and more accurate environmental risk assessment requires greater consideration of the natural water physico‐chemistry in which the organisms we seek to protect live.